ERK-dependent phosphorylation of HSF1 mediates chemotherapeutic resistance to benzimidazole carbamates in colorectal cancer cells. Issue 6 (July 2015) - Wales, Christina T.K.; Taylor, Frederick R.; Higa, Allan T.; McAllister, Harvey A.; Jacobs, Aaron T.
Abstract : Drugs containing the benzimidazole carbamate scaffold include anthelmintic and antifungal agents, and they are now also recognized as having potential applications in the treatment of colorectal and other cancers. These agents act by binding to β-tubulin, and in doing so they disrupt microtubules, arrest cell division, and promote apoptotic cell death in malignant cells. We have evaluated several commercially available benzimidazole carbamates for cytotoxic activity in colorectal cancer cells. In addition to cytotoxicity, we also observe activation of the transcription factor, heat shock factor-1 (HSF1). HSF1 is well known to mediate a cytoprotective response that promotes tumor cell survival and drug resistance. Here, we show that biochemical inhibition with the HSF1 inhibitor KRIBB11 or siRNA-based silencing of HSF1 results in a significant enhancement of drug potency, causing an approximately two-fold decrease in IC50 values of parbendazole and nocodazole. We also define a mechanism for drug-induced HSF1 activation, which results from a phosphorylation event at Ser326 that is dependent on the activation of the extracellular regulated protein kinase-1/2 (ERK-1/2) mitogen-activated protein kinase pathway. Inhibition of the upstream kinase MEK-1/2 with U0126 attenuates the phosphorylation of both ERK-1/2 and HSF1, and significantly enhances drug cytotoxicity. From these data we propose a unique model whereby the ERK-1/2-dependent activation of HSF1 promotes chemotherapeutic resistance to benzimidazole carbamates. Therefore, targeting the ERK-1/2 signaling cascade is a potential strategy for HSF1 inhibition and a means of enhancing the cytotoxicity of these agents.